PENGARUH LEVEREGE DAN PROFITABILITAS TERHADAP KEPUTUSAN HEDGING PERUSAHAAN MANUFAKTUR INDONESIA - Jiwandhana, RM Satwika Putra; Triaryati, Nyoman (E-Jurnal Manajemen; Vol 5 No 1 (2016), 2016)
This study tested financial distress hypothesis which states that financial distress can be minimized if the company conducts hedging activities with derivatives instruments. This study aimed to test the financial distress hypothesis in manufacturing companies in Indonesia Stock Exchange in 2010 until 2013. Sampling using purposive sampling techniques, according to the criteria established company obtained 125 samples and 500 firm-year observation. Logistic regression was used to test the financial distress hypothesis. The results show that the variable debt to equity ratio as a proxy for leverage has a negative effect, but not statistically significant for hedging activity, while the variable return on assets as a proxy for profitability have a positive influence and significant for hedging activity.
Keywords: financial distress; leverage; profitability; hedging